Investigation on the possibility of obtaining of motor fuels from bituminous sand by heat treatment - Jadamba, D; Ulzii, B; Tuya, M (Mongolian Journal of Chemistry, 2014)
DOI: http://dx.doi.org/10.5564/mjc.v12i0.182 Mongolian Journal of Chemistry Vol.12 2011: 102-106